(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2026)
The image of risk-taking travellers has traditionally been ascribed to men. This study seeks to examine how contemporary Indian women’s photo-travelogues, Zanskar to Ziro: No Stilettos in the Himalayas by Sohini Sen and Walking in Clouds: A Journey to Mount Kailash and Lake Manasarovar by Kavitha Yaga Buggana, disrupt gendered notions of adventure travel. Utilising theoretical frameworks of women’s travel writings, spatiality studies and feminist geography, the study argues how, in the 21st century, intrepid Indian women navigate unfamiliar, rugged and ostensibly inaccessible terrains in South Asia, exhibiting willingness to take on challenges despite their vulnerability. The spaces in the texts appear not merely as backdrops but as dynamic heterogeneous sites, as the study emphasises that spatiality shapes women’s travel narratives, wherein hostile and extreme landscapes function as a source of adversity and autonomy. The external terrain serves as a reflection, analogy, extension and at times, an antithesis of the traveller-authors’ internal realities. A critical interpretation and photo-textual analysis will demonstrate how Indian women travellers remap, reimagine and remake unfamiliar terrains. The study contributes to a nuanced understanding of tenacious Indian women travellers, who dismantle stereotypes and map novel avenues for female empowerment and resilience using illustrative storytelling.